An Evaluation of the Maintenance of Peace and Order in Nueva Ecija Provincial Jail - A. Austria-cruz, Mary Chris; P. Reyes, MA. Cecilia (International Journal of English Literature and Social Sciences (IJELS), 2019)
The study was conducted in the Nueva Ecija Provincial Jail (NEPJ) located at Caalibangbangan, Cabanatuan City, Nueva Ecija. Ninety (90) inmates and ten (10) jail personnel served as respondents of the study. The NEPJ provides the strict implementation of the rules and regulations in the custody and security of inmates. Both provincial personnel and inmates know that all the security procedures in the jail activities are highly implemented. A prisoner accused of breaking the rules does not have all the rights during the trial because a prison disciplinary proceeding is not the same as in criminal prosecution[1]. Among other things, the researchers recommended that the administration of NEPJ should continue the way and manner on how they provide very effective security operation, as well as in maintaining the activities that help the inmates make a better relationship with the provincial jail and other inmates.